The significance of outcrop analog data for reservoir quality assessment: A comparative case study of Lower Triassic Buntsandstein sandstones in the Upper Rhine Graben. (July 2022) - Busch, Benjamin; Spitzner, Alexander-David; Adelmann, Dirk; Hilgers, Christoph
Abstract: Subsurface reservoir quality assessments are among the most important workflows in reservoir geology. The application has been standard practice in the hydrocarbon industry and is also adopted for geothermal reservoir systems hosted in clastic rocks. With the emergence of fluid mining for metals, such as lithium for the energy transition, yet another field may adopt the standard practice. However, as drill cores and hard geological data from the subsurface are expensive commodities they may be substituted by outcrop analog studies to fill in data gaps in the understanding of the deep subsurface. However, reservoir quality controls, such as pore-filling cements or natural fractures may be altered or overprinted during uplift to the surface and exposure to undersaturated meteoric fluids and associated stress release. A complete understanding of geochemical and geomechanical processes affecting the rocks since their deposition is needed to account for that, otherwise data may not be representative of the subsurface. In this case study using petrographic (point-counting) and petrophysical (porosity and permeability) analyses we highlight the possibilities and limitations of outcrop analog data used for the evaluation of subsurface reservoir quality. The focus is on the Triassic Buntsandstein within the Upper Rhine Graben in southwestern Germany and eastern France and exposed outcrop analogs along the western margin of the graben. Here, we show that some data (detrital composition, quartz cement, K-feldspar cement, and clay mineral cement volumes) may directly be applicable to subsurface reservoir quality assessment. However, other data (porosity, permeability, IGV, carbonate cement, and iron hydroxide cement contents) cannot be used analogously to subsurface samples and we outline possible approaches to mitigate some of the mismatches in the frame of a reservoir quality study. In particular, the correction for uplift diagenetic dissolution of carbonate cemented nodules and goethite precipitation will be the key to gain more accurate results in the presented area. Highlights: Outcrop analog data can partially be used to assess RQ controls in the subsurface. Quartz-, K-feldspar- and clay mineral cement volumes may be extracted from outcrop samples. Detrital compositions, grain coating coverages and their effect on cementation and compaction are comparable. Carbonate cements (dissolved) and iron hydroxides (precipitated) are the main mismatch in authigenic components. Absolute values for IGV, porosity, and permeability are not transferable.